2002
DOI: 10.1046/j.1365-2605.2002.00338.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of foetal‐onset hypothyroidism on the epididymis of mature rats

Abstract: It is well established that congenital hypothyroidism leads to male infertility. However, there is a dearth of information on foetal-onset hypothyroidism-induced changes in the epididymis. With regard to transient hypothyroidism, the existing literature deals mainly with the testis. However, it is not known whether there is any corresponding alteration in epididymal morphology and physiology under such a condition. The present study is therefore aimed at understanding the impact of persistent and transient hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 39 publications
2
22
0
2
Order By: Relevance
“…Methimazole (MMI, 0.05% in drinking water) was used to induce hypothyroidism (21)(22)(23). The rats were divided into the following groups: group I: control rats at PND 120, not exposed to MMI; group II: MMI treatment to pregnant dams from ED 9 to ED 14, covering the period of fetal testicular differentiation; group III: MMI treatment from ED 9 to ED 18, covering the period of initial differentiation of epididymis from the Wolffian duct; and group IV: MMI treatment from ED 9 to ED 21, covering the entire period of fetal differentiation of the reproductive tract organs.…”
Section: Induction Of Hypothyroidismmentioning
confidence: 99%
See 1 more Smart Citation
“…Methimazole (MMI, 0.05% in drinking water) was used to induce hypothyroidism (21)(22)(23). The rats were divided into the following groups: group I: control rats at PND 120, not exposed to MMI; group II: MMI treatment to pregnant dams from ED 9 to ED 14, covering the period of fetal testicular differentiation; group III: MMI treatment from ED 9 to ED 18, covering the period of initial differentiation of epididymis from the Wolffian duct; and group IV: MMI treatment from ED 9 to ED 21, covering the entire period of fetal differentiation of the reproductive tract organs.…”
Section: Induction Of Hypothyroidismmentioning
confidence: 99%
“…Recent studies have shown the presence of specific T 3 receptors in the epididymis of rats (20). Another study from our laboratory (21) emphasized the need for optimum thyroid function during prenatal and postnatal period to have normal androgen status in the epididymis of adult rats.…”
mentioning
confidence: 99%
“…Direct eVects of TH have also been reported in the rat epididymis, a component of the testicular excurrent duct system, the epididymis is a highly specialized organ involved in the transport, maturation, and storage of spermatozoa (Del Rio et al 2000;Kala et al 2002;St-Pierre et al 2003). The epididymal epithelium contains several cell types: principal, basal, clear, narrow, halo and apical cells.…”
Section: Introductionmentioning
confidence: 96%
“…Even though direct eVects of TH have been reported in the rat epididymis (Del Rio et al 2000;Kala et al 2002;StPierre et al 2003) as well as in other cells of the male reproductive system, TR localization was only reported for Leydig and Sertoli cells (Hardy et al 1996;. The goals of the present study were: (1) to assess whether epididymal epithelial cells from the diVerent areas of epididymis express TR ( -( isoforms, (2) to depict their subcellular immunolocalization, and (3) to evaluate if the TR expression is modiWed when rats are submitted to hypothyroid state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation